CEP57 mutation in a girl with mosaic variegated aneuploidy syndrome. Issue 1 (20th November 2013) - Pinson, Lucile; Mannini, Linda; Willems, Marjolaine; Cucco, Francesco; Sirvent, Nicolas; Frebourg, Thierry; Quarantotti, Valentina; Collet, Corinne; Schneider, Anouck; Sarda, Pierre; Geneviève, David; Puechberty, Jacques; et al.
<x xml:space="preserve">Abstract</x> Mosaic variegated aneuploidy (MVA) is a rare autosomal recessive disorder characterized by constitutional aneuploidies. Mutations in BUB1B and CEP57 genes, which are involved in mitotic spindle and microtubule stabilization, respectively, are responsible for a subset of patients with MVA. To date, CEP57 mutations have been reported only in four probands. We report on a girl with this disorder due to c.915‐925dup11 mutation in CEP57, which predicts p.Leu309ProfsX9 and review the literature in order to facilitate genotype–phenotype correlation. Rhizomelic shortening of the upper limbs, skull anomalies with conserved head circumference, and absence of tumor development could be features suggesting a need for molecular screening of the CEP57 gene in patients with this disorder. © 2013 Wiley Periodicals, Inc.